1984
DOI: 10.1126/science.6429856
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cholesterol Crystal Formation by Apolipoproteins in Supersaturated Model Bile

Abstract: Apolipoproteins A-1 and A-2 were purified from human plasma. At concentrations present in human bile these proteins prolonged the nucleation time of cholesterol monohydrate crystals when added to model systems of supersaturated bile. In contrast, apolipoprotein C-3 and other serum proteins did not have this effect. Also, when human gallbladder bile was fractionated by gel filtration chromatography, apolipoproteins A-1 and A-2 were among the proteins present in a fraction of bile enriched in potent inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(60 citation statements)
references
References 18 publications
3
56
0
1
Order By: Relevance
“…Apo Al and apo All are secreted in bile (67). Very recently, it was reported that apo Al and apo All in supersaturated gallbladder bile inhibit the rate of formation of solid cholesterol crystals (68). This evidence suggests that the A apolipoproteins can prevent cholesterol gallstone formation.…”
Section: Discussionmentioning
confidence: 89%
“…Apo Al and apo All are secreted in bile (67). Very recently, it was reported that apo Al and apo All in supersaturated gallbladder bile inhibit the rate of formation of solid cholesterol crystals (68). This evidence suggests that the A apolipoproteins can prevent cholesterol gallstone formation.…”
Section: Discussionmentioning
confidence: 89%
“…However, few other details are known about the adsorption process. A better understanding of the antifreeze adsorption may also provide insights into the mechanisms of other proteins that (i) inhibit the growth of biocrystals, such as bone minerals (8,9), enamel (10), cholesterol crystals (11), and kidney stones (12); and (ii) act as crystal nucleators (13,14), since the processes of nucleation and growth inhibition are closely related (13).…”
mentioning
confidence: 99%
“…Biliary apoA-I possesses antinucleating properties, although the mechanisms by which apoA-I inhibits cholesterol crystallization and stone formation are not well defined (16,21). ApoA-I is transported from the AP to the BL side of human and murine GBEC (50), although this was not confirmed in our GBEC system (32).…”
Section: Discussionmentioning
confidence: 59%